STRUCTURING GLOBAL ISLAMIC FINANCE: A PHILOSOPHICAL PERSPECTIVE ON REGULATION AND STANDARDIZATION - Amrullah; Arinal Rahmati; Wahyu Ichsan (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This study examines the regulation and standardization of the global Islamic economy through a philosophical lens grounded in maqashid al-shariah as the primary foundation for building a financial system that is just, transparent, and sustainable. The research background is rooted in the rapid growth of the global Islamic financial industry, which continues to face challenges including regulatory fragmentation, divergent standards across jurisdictions, and the dominance of formal compliance approaches that do not fully reflect the substantive values of Sharia. This study aims to analyze the philosophical underpinnings of Islamic economic regulation, the problematics of global standardization, and the gap between Islamic normative values and the practices of modern financial industries. A qualitative research approach with a library research design was employed, utilizing analysis of academic literature, regulatory documents, scientific journals, and reports from international institutions. The findings indicate that regulatory harmonization and maqashid al-shariah-based standardization are essential for strengthening the legitimacy, stability, and integration of the global Islamic financial system. This study further affirms the importance of reconstructing regulations that are oriented not only toward administrative compliance but also toward ethical values, social justice, and sustainable development in the face of modern economic dynamics